Parental bereavement: A comparison between mothers and fathers' grief experiences and coping strategies after a death of a child due to cancer - Cruz, Roxanne H. (Animo Repository, 2007)
In this study, the researchers described the similarities and differences of Filipino mothers and mothers in their grief experience and ways of coping upon the death of a child due to cancer. Ten parents, composed of 5 mothers and 5 fathers, were interviewed. Qualitative content analysis was used to analyze and find themes in the data gathered. Results show that in the grief experience, both mothers and fathers experienced panghihinayang and experienced intense pain. However, they differ in terms of the mothers' experience along the themes of prior of death, pain avoiding grief, and unresolved grief, and the fathers' experience of enduring and short-term grief. Findings on coping strategies showed that seeking social support and faith-based coping are similar in both parents. The differences in coping involve the mothers' preference to be isolated and preoccupied in contrast with the fathers' preference to look and be strong, the use of humor, and the drive to improve the life of the remaining family members.